The Impact Of Lean Manufacturing On Operational Performance Through Vendor-Managed Inventory And Supply Chain Practices - FOKALI, CHRISTIAN; SIAGIAN, HOTLAN (The journal of contemporary issues in business and government, 2021)
This study investigates the impact of lean manufacturing on operational performance through vendor-managed inventory and supply chain practices as the mediating variable. The study used the population of the manufacturing company domiciled in east Java, Indonesia. Data collection used a questionnaire designed with a five-point Likert scale. The study sample is 111 manufacturing companies from 5420 manufacturing companies domiciled in East Java. Data analysis used partial least square (PLS) technique using smarPLS software version 3.3. The result indicated that nine hypotheses developed were supported in this study. Lean manufacturing affects vendor-managed inventory, supply chain practices, and operational performance. Vendor- managed inventory and supply chain practices directly affect operational performance. Lean manufacturing indirectly improves operational performance through the mediating role of vendor-managed inventory and supply chain practices. This research provides a managerial implication on how to improve the operational performance in supply chain management. This study also could contribute to the current supply chain management theory.